The comprehensive assessment of the prevalence of metabolic syndrome in obese children and adolescents - Aliusef , Maiia; Churylina , Alina (The Ukrainian Scientific Medical Youth Journal, 2023)
childhood obesity is recognized as a significant health concern by the WHO, but not all obese individuals face the same risk of cardiometabolic disorders.  This study aims to diagnose metabolic syndrome (MetS) in obese children according to various known definitions and to determine the influence of all five definitions of MetS on insulin resistance using logistic regression models. The observational cross-sectional study on 82 children aged 12 to 17 with obesity was conducted at the Children’s Clinical Hospital No.6 in Kyiv. MetS was established according to five main definitions. All biochemical analyses were performed using the enzymatic colorimetric method by Cobas 6000, Roche Diagnostics (Switzerland). The prevalence of MetS among children with obesity was higher using the de Ferranti et al. (76.8%) definition and the lower using Viner et al. definition (29.3%), p=0.023. The construction of a logistic regression model showed that having all the components of MetS according to different definitions, children and adolescents are likely to have a HOMA-2 above 2.26 (AUC more significant than 0.5, p<0.05). Different prevalence of MetS was found, depending on the different approaches to diagnosis. The construction of a logistic regression model showed that the parameters of the metabolic syndrome influence the risk of high HOMA-2 IR using four of five definitions.